DOSTOIEVSKI ENTRE O CRISTIANISMO "ROSY" E O GNOSTICISMO - Ivanova Dimitrova, Nina (Eleuthería - Revista do Curso de Filosofia da UFMS, 2016)
This article discusses Dostoyevsky’s ambivalent attitude to the world, his Gnostic assertions, and his world-accepting attitude. The author presents arguments supporting the conclusion that love for the world was the predominant attitude of Dostoyevsky, and clarifies the polysemantic concept of “world”. This attitude in Dostoyevsky is used to explain the strong attraction and reverence he felt for the “Russian startsi” phenomenon as an alternative to traditional monasticism and as an institution on which he set hopes that it might bring the Church closer to the “world”. The article presents some critical assessments made from the viewpoint of Orthodox doctrine regarding Dostoyevsky’s depiction of Russian “startsi” in his works.